Modeling the Load of the Kinematic Pair Piston-cylinder in an Axial Piston Pump by Means of FEA. (2017) - Zloto, Tadeusz; Stryjewski, Piotr
Abstract: The paper analyses the load of the kinematic pair piston-cylinder in an axial piston pump. To determine equivalent stress between the piston and cylinder, a commercially available software ADINA was applied. It was also used for constructing numerical models and representing the results of the study.